Association of alkaline-phosphatase/albumin ratio with all-cause mortality in critically ill patients with ischemic stroke: a retrospective study - Zheng, Tao; Guo, Mengmeng; Han, Yating; Li, Guanglu; Wang, Xianhua; Li, Shenjie; Gao, Yuting; Tang, Wenxiong; Liu, Zunjing (Frontiers in Neurology, 2025)
BackgroundRecent studies have shown that alkaline phosphatase to albumin ratio (APAR) is a prognostic biomarker for coronary heart disease and cancer. However, the effect of APAR on the prognosis of ischemic stroke (IS) remains unclear. We aimed to assess the association of APAR with all-cause mortality in critically ill patients with IS.MethodsCritically ill patients with IS were identified from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) Version 3.0 database, and classified into quartiles based on APAR index levels. Clinical outcomes included all-cause mortality at 28-days, 90-days and 365-days after admission. Cox proportional hazards regression analysis and restricted cubic spline method were used to clarify the relationship between APAR index and clinical outcomes in critically ill patients with IS.ResultsA total of 1,690 critically ill patients with IS were selected from the MIMIC-IV database. Multivariate Cox proportional hazard analysis showed that increased APAR index was significantly associated with all-cause mortality. After adjusting for potential confounding factors, patients with higher APAR (Q4: 1.524–2.794) had significantly increased all-cause mortality at 28-days, 90-days, and 365-days after admission (HR 2.05, 95%CI 1.47–2.86, p = 0; HR 2.09, 95%CI 1.53–2.85, p = 0; HR 2.11, 95%CI 1.55–2.87, p = 0). APAR had a linear relationship with 28-days and 365-days mortality (P for non-linearity: 0.098 and 0.051), but a nonlinear relationship with 90-days mortality (P for non-linearity: 0.042). Subgroup analyses further revealed that higher APAR was also associated with increased long-term mortality in IS patients without hypertension, DM, cardiovascular disease, liver disease or CKD. In addition, we did not observe any interaction between subgroup variables and APAR.ConclusionA higher APAR index was significantly associated with increased all-cause mortality at 28-days, 90-days and 365-days after admission for critically ill patients with IS. The APAR index may help identify patients with IS at high risk of all-cause death.